Structure-sensitive enantiospecific adsorption on naturally chiral Cu(hkl)R&S surfaces. (15th November 2016) - Gellman, Andrew J; Huang, Ye; Koritnik, Anjanette J; Horvath, Joshua D
Abstract: The desorption kinetics of a chiral compound, R -3-methylcyclohexanone ( R -3MCHO), have been measured on both enantiomers of seven chiral Cu( hkl ) R & S surfaces and on nine achiral Cu single crystal surfaces with surface structures that collectively span the various regions of the stereographic triangle. The naturally chiral surfaces have terrace-step-kink structures formed by all six possible combinations of the three low Miller index microfacets. The chirality of the kink sites is defined by the rotational orientation of the (1 1 1), (1 0 0) and (1 1 0) microfacets forming the kink. R -3MCHO adsorbs reversibly on these Cu surfaces and temperature programmed desorption has been used to measure its desorption energetics from the chiral kink sites. The desorption energies from the R - and S -kink sites are enantiospecific, Δ Δ E des S − R = Δ E des S − Δ E des R ≠ 0, on the chiral surfaces. The magnitude of the enantiospecificity is | Δ Δ E des S − R | ≈ 1 kJ mol −1 on all seven chiral surfaces. However, the values of Δ Δ E des S − R are sensitive to elements of the surface structure other than just their sense of chirality as defined by the rotational orientation of the low Miller index microfacets forming the kinks; Δ Δ E des S − R changes sign within the set of surfaces of a given chirality.